Supporting the mental health of children with speech, language and communication needs: The views and experiences of parents. (May 2022) - Hobson, Hannah; Kalsi, Mya; Cotton, Louise; Forster, Melanie; Toseeb, Umar
Background and aims: A high rate of children in mental health services have poor language skills, but little evidence exists on how mental health support is delivered to and received by children with language needs. This study looked at parental experiences, asking parents of children with speech, language and communication needs (SLCN) about their experiences seeking help for their children's mental health. We were particularly interested on the experiences of parents of children with Developmental Language Disorder (DLD), a specific SLCN that remains relatively unknown to the general public. Methods: We conducted an online survey of 74 parents of children with speech, language and communication needs (SLCN). Survey respondents included parents of children with a range of difficulties, including DLD, autism, verbal dyspraxia, global intellectual delay, a history of hearing problems, and SLCN without a primary diagnosis. Survey respondents were asked what sources of support they had accessed for their child's mental health and to provide comments on what was good and what was not good about this support. We then conducted 9 semi-structured interviews of parents of children with DLD about their experiences. These were parents of children with DLD aged 7 to 17 years, from across a range of educational settings, and with a range of present mental health concerns. Results: Content analyses of the survey responses from parents of children with SLCN highlighted three broad factors of importance to parents' experiences: relational aspects of care, organisational aspects of care, and professionals' knowledge. Thematic analyses of the interviews of parents of children with DLD identified 5 themes: the effects of language problems on the presentation of distress; the role of the school environment; the role of key professionals; standard approaches to mental health support might not be appropriate; and the role and impact on parents. Parents expressed concerns that their children's mental health problems and need for support would not be recognised, and felt interventions were not accessible, or delivered in a manner that was not comfortable for their children due to high reliance on oral language skills. Some parents were left feeling that there was no provision suitable for their children. Conclusions: Parents of children with SLCN face barriers accessing support for their children's mental health, including a lack of professional knowledge about their children's language needs. Parents argued that language and communication needs can significantly affect the delivery and success of psychological therapies and interventions. Systematic research is needed to understand how to successfully adapt services to make them accessible to children and young people with language needs, and to ensure that mental health problems are detected in children with language difficulties. Increased knowledge about language disorders such as DLD, and access to speech and language therapy expertise, is needed amongst professionals who work to support children's mental health.